No longer any role for routine follow-up chest x-rays in men with stage I germ cell cancer. (October 2017) - De La Pena, H.; Sharma, A.; Glicksman, C.; Joseph, J.; Subesinghe, M.; Traill, Z.; Verrill, C.; Sullivan, M.; Redgwell, J.; Bataillard, E.; Pintus, E.; Dallas, N.; et al.
Abstract: Following radical orchidectomy for testicular cancer, most patients undergo protocolled surveillance to detect tumour recurrences rather than receive adjuvant chemotherapy. Current United Kingdom national and most international guidelines recommend that patients require a chest x-ray (CXR) and serum tumour markers at each follow-up visit as well as regular CT scans; there is however, variation among cancer centres with follow-up protocols. Seminomas often do not cause tumour marker elevation; therefore, CT scans are the main diagnostic tool for detecting relapse. For non-seminomatous tumours, serum beta-HCG (HCG) and AFP levels are a very sensitive harbinger of relapse, but this only occurs in 50% of patients [1], and therefore, imaging remains as important. CXRs are meant to aid in the detection of lung recurrences and before the introduction of modern cross-sectional imaging in the early 1980s, CXRs would have been the only method of identifying lung metastasis. We examined the Thames Valley and Mount Vernon Cancer Centre databases to evaluate the role of CXRs in the 21st century for the follow-up of men with stage I testicular cancer between 2003 and 2015 to assess its value in diagnosing relapsed germ cell tumours. From a total of 1447 patients, we identified 159 relapses. All relapses were detected either by rising tumour markers or planned follow-up CT scans. Not a single relapse was identified on CXR. We conclude that with timely and appropriate modern cross-sectional imaging and tumour marker assays, the CXR no longer has any value in the routine surveillance of stage I testicular cancer and should be removed from follow-up guidelines and clinical practice. Omitting routine CXR from follow-up schedules will reduce anxiety as well as time that patients spend at hospitals and result in significant cost savings. Highlights: Surveillance schedules to detect germ cell cancer relapse following surgery for Stage I germ cell tumour are important. The identification mode for 159 relapses from 1447 Stage I germ cell tumour patients on surveillance are presented here. Not a single relapse was detected by CXR alone. CXR should be removed from Stage I GCT surveillance guidelines. In line with practising evidence-based medicine, this data has changed our practice already. Omitting CXR from surveillance in stage I GCT, reduces radiation exposure and patient anxiety and lowers costs.